Regulation of The Minister of Finance of The Republic of Indonesia Number 131 of 2024 on The Increase of Vat By 12% and Its Impact - Rezkiyanti, Nur Alfiah; Hutabarat, Emayanti Cristina; Natalia, Desy; Hasriadi, L.M; A.Tao, Tantaka (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2025)
The increase in the Value Added Tax (VAT) rate to 12% planned for 2025 is part of the tax reform efforts outlined in the Harmonization of Tax Regulations Law (UU HPP). This policy aims to increase state revenue, support national development, and create a fairer tax system. In addition, the increase in VAT rates is expected to strengthen the government's fiscal resilience in facing global economic challenges, including economic uncertainty and the need for financing for strategic infrastructure projects. This reform also aims to align domestic tax policies with international standards to enhance Indonesia's economic competitiveness and attract more foreign investment. PMK 131 of 2024 states that the increase in the Value Added Tax (VAT) rate to 12% will not be applied universally, but only to luxury goods. The government maintains the principle of fairness by providing different tax treatments for various types of goods and services. For luxury goods, VAT is calculated at the full rate of 12% of the selling price or import value, with a transition period until January 31, 2025, during which the effective rate remains 11% through another value mechanism of 11/12 of the selling price. Meanwhile, for goods other than luxury goods, services, and intangible goods, VAT is imposed at a rate of 12%, but calculated using the DPP value of 11/12 of the import value, selling price, or replacement value, so the effective rate remains 11%. In addition, there are exceptions for certain Taxable Goods (BKP) and Taxable Services (JKP) that are subject to VAT with a different DPP value or specific amounts, such as 3 kg LPG, gold jewelry, and used motor vehicles, which will continue to follow the previous regulations and are not affected by this policy. This change also impacts the tax administration system, including the use of tax invoice serial number codes from 010 to 040 for transactions with different taxable base values. With this policy, the government is striving to balance the need to increase state revenue with maintaining the purchasing power of the public and the continuity of businesses. The transition period for luxury goods shows the government's efforts to provide adaptation before the full implementation of the 12% VAT rate